Matrix transformations from absolutely convergent series to convergent sequences as general weighted mean summability methods - Jinlu Li (International Journal of Mathematics and Mathematical Sciences)
We prove the necessary and sufficient conditions for an infinity matrix to be a mapping, from absolutely convergent series to convergent sequences, which is treated as general weighted mean summability methods. The results include a classical result by Hardy and another by Moricz and Rhoades as particular cases.